Antibacterial efficacy of Mangifera indica L. leaves extract against Streptococcus mutants - Pramusita, Adya; Yunus, Renna Maulana; Mukharromah, Lailatul; Andriana, Agustin (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background: Various preventive actions are being developed to prevent dental caries. On the other hand, some of these methods can only be applied by the dentist. Therefore, it is necessary to find an alternative caries prevention method. Purpose: This study aimed to determine the antibacterial activity of mango (Mangifera indica L.) leaves extract in inhibiting the growth of Streptococcus mutans. Methods: This research is experimental laboratory research and used a random sampling technique. Mango (M. indica L.) leaves extract was diluted using the double dilution method, which were 50%, 25%, 12.5%, 6.25%, 3.12%, 1.6%, 0.8%, 0.4%, 0.2%, 0.15%, 0.1%, 0.05%, and 0.025%. The Minimum Bactericidal Concentration (MBC) of mango (M. indica L.) leaves extract against S. mutans was determined using the agar plate thinning method. Results: The results showed no bacterial growth in the media with 100%, 50%, and 25% mango leaves extract. In addition, it was found that in media with 12.5% mango leaves extract still showed colony growth. Conclusion: Mango (M. indica L.) leaves extract in ethanol solvent has an antibacterial effect against S. mutans with the MBC value of 25%.